Efficacy of CDK4/6 Inhibition in colorectal cancer and the role of p16 expression in predicting drug resistance - Julia Schneider; Najib Ben Khaled; Liangtao Ye; Ralf Wimmer; Linda Hammann; Alexander Weich; Christoph Suppan; Ujjwal Mukund Mahajan; A. W. Jung; Jörg Kumbrink; Gerald Denk; Monika Rau; et al. (2025)
Abstract Introduction Colorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. The use of sequential polychemotherapies has improved the survival of patients with advanced metastatic disease. However, the survival rates achieved are low, and chemotherapy-related side effects are significant. Therefore, new, efficient, and tolerable therapies are urgently needed. In this study, we investigate the efficacy of pharmacological cyclin D-dependent kinase (CDK) 4/6 inhibition and explore the relevance of p16 as predictors of susceptibility to CDK 4/6 therapy. Materials and methods CDK 4/6 inhibitors were evaluated in native and FOLFOX- or ribociclib-resistant CRC, hepatocellular carcinoma (HCC), and breast cancer (BC) cell lines using viability, colony formation, and flow cytometry (FC)-based assays. Western blotting was employed to assess the expression of Rb and members of the INK4 family. SiRNA-based knockdown of CDK4/6 was utilized to gain insights into mechanisms of action or resistance. Tissue from 185 CRC patients was examined for the expression of p16 and its relevance for progression-free and overall survival. The prognostic relevance of cyclin-dependent kinase inhibitor 2 A ( CDKN2A ) mRNA expression data was derived from The Cancer Genome Atlas (TCGA) data. Results Ribociclib demonstrates significant antitumoral effects in various CRC, HCC, and BC cell lines, similar to two other approved CDK4/6 inhibitors (palbociclib and abemaciclib). Ribociclib-resistant cell lines (Hep-3B, HCC-1937, and BT-549) exhibited higher p16 expression compared to ribociclib-sensitive cell lines. In ribociclib-sensitive cell lines, CDK4/6 inhibition led to G1 phase arrest, whereas resistant cells did not exhibit such effects. A similar phenotype could be observed upon dual siRNA based CDK4/6 knockdown in ribociclib-sensitive HuH-7 and ribociclib-resistant Hep-3B cell lines. All CRC cell lines tested showed sensitivity to ribociclib, including the FOLFOX-resistant SW620 cell line. Low mRNA expression of CDKN2A (p16) was associated with favorable prognosis in CRC patients. No prognostic significance was found for p16 protein expression in an early-stage CRC cohort ( n = 185). Conclusion Ribociclib demonstrates significant antitumoral effects across a large panel of cancer cell lines and chemoresistant models, especially in CRC. Resistance towards ribociclib is associated with high p16 expression, which is a negative prognostic marker for patients with CRC. Our findings underscore p16 as a promising biomarker for predicting ribociclib responsiveness and emphasize the need for further mechanistic studies and combination therapy approaches to overcome resistance in p16 high patients.